2018
DOI: 10.1186/s12889-018-5373-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of latent tuberculosis infection among coal workers’ pneumoconiosis patients in China: a cross-sectional study

Abstract: BackgroundLittle is known about the prevalence of latent tuberculosis infection (LTBI) among coal workers’ pneumoconiosis (CWP) patients. To estimate the prevalence of LTBI and identify its associated risk factors among CWP patients.MethodsA cross-sectional study was conducted to assess the prevalence of LTBI. Participants were screened for active TB or a history of TB by X-ray and those that underwent QuantiFERON-TB Gold In-Tube (QFT) test. A standardized questionnaire was completed and risk factors were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
1
9
0
2
Order By: Relevance
“…Coal workers with chronic exposure to coal dust often present a variety of respiratory illnesses. The main disease is pneumoconiosis and the most common complication is pulmonary tuberculosis [ 2 ]. Therefore, in previous reports [ 3 ], chest radiographs and CT images often showed multiple pulmonary nodules, interstitial fibrosis and emphysema.…”
Section: Resultsmentioning
confidence: 99%
“…Coal workers with chronic exposure to coal dust often present a variety of respiratory illnesses. The main disease is pneumoconiosis and the most common complication is pulmonary tuberculosis [ 2 ]. Therefore, in previous reports [ 3 ], chest radiographs and CT images often showed multiple pulmonary nodules, interstitial fibrosis and emphysema.…”
Section: Resultsmentioning
confidence: 99%
“…( 13 ) Another study evaluated 244 patients with coal workers' pneumoconiosis and found a positive IGRA in 162 (66.4%) of them. ( 14 ) There are no studies on LTBI in patients with other types of ILD. It is not possible to ascertain whether the prevalence found in our study reflects the true prevalence in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that the latent infection rate of PTB in patients with pneumoconiosis is 65%, which was significantly higher than that in the general population (20%). [ 34 ] It is recommended that clinicians evaluate for LTBI and the immune status of the patient before using hormone drugs for pneumoconiosis.…”
Section: Discussionmentioning
confidence: 99%